Contributions Of Metacognitive Skills Toward Studentsâ Cognitive Abilities Of Biology Through The Implementation Of GITTW (Group Investigation Combined With Think Talk Write) Strategy - Listiana, Lina; Susilo, Herawati; Suwono, Hadi; Suarsini, Endang (Proceeding of International Conference on Teacher Training and Education, 2016)
Metacognitive skill is an important aspect that must be developed and empowered in learning activities because it helps the development of thinking skills as well as its implications on studentsâ cognitive abilities. Therefore, the learning process should be designed to empowered metacognitive skills. This is a correlational study which aims to find (1) the relationship of metacognitive skills with cognitive abilities of Biology, and (2) the contribution of metacognitive skills on cognitive abilities of Biology on the application of the GI, TTW and GITTW strategies. The population of this study is Muhammadiyah high school students of grade 10th at Surabaya in the 1st academic year 2014/2015 in the science major. Samples were students of grade 10th which consists of six classes determined by random sampling. Data had been collected by conducting pre-test and posttest during the learning process for one semester. Learning instruments used in this study are syllabus, lesson plan (RPP), and studentsâ worksheet (LKS). All learning devices are using GI, TTW and GITTW strategies. The forms of instruments used are an essay test and cognitive skills rubrics. Metacognitive skills had been measured by metacognitive rubric integrated with cognitive ability test. Data was analysed by correlation and regression techniques. The results of the study showed that there were a significant correlation between metacognitive skills with cognitive abilities of Biology in GI strategy with a correlation coefficient (r) of 0.906, the TTW strategies correlation coefficient (r) of 0.951 and the strategies GITTW correlation coefficient (r) of 0.881. Metacognitive skill level of contribution to the cognitive abilities of Biology at GI strategy is 82%, the TTW strategy is 90.5%, and the GITTW strategy is 77.7%.